‘Not disabled enough’: Episodic disabilities and the Ontario Disability Support Program - Lightman, Ernie; Vick, Andrea; Herd, Dean; Mitchell, Andrew (Disability Studies Quarterly, 2009)
Persons living with episodic disabilities who apply for long-term income assistance in Ontario, Canada are often denied eligibility because of the questionable legitimacy of their shifting medical conditions. Since there are no official categories for persons with episodic disabilities to fit in because they are not entirely well (and employable) nor entirely sick (and unemployable), they are judged as ‘not disabled enough’ within the existing parameters of assistance. Drawing on a series of longitudinal, semi-structured interviews with eight respondents in Toronto, all of whom applied for, but were denied, long-term assistance, we examine the tension between how episodic disabilities are embodied versus the manner in which ‘disability status’ is legislatively constructed. Implications reconsidering the logistics of fixed categories and strategies addressing the wider spectrum of the experience of disability for policy are addressed. Keywords: disability, episodic, Ontario Disability Support Program, ODSP, definitions, embodiment, legitimate